Kekuasaan Presiden Dalam Pembentukan Kabinet Menurut Sistem Presidensial - Kelmaskosu, Krisyando; Rauta, Umbu (JURNAL USM LAW REVIEW, 2025)
This study aims to discuss the president's power in forming a cabinet in connection with the amendment to Law No. 39 of 2008 concerning State Ministries (Ministry Law). One of the main changes to the law is Article 15 concerning the total number of ministries, which was originally limited to a maximum of 34 ministries, changed according to the needs of the administration of government by the President. The norm does not explicitly regulate the total number of ministries. This is indeed compatible or in line with the presidential system of government firmly adopted by Indonesia after the constitutional amendment in 2002. The problems arising from the change in the norm are related to the implications of increasing the number of ministries which are related to governance. The change in this article refers to legalistic, not prerogatives because if it is prerogative, the number of ministries does not need to be regulated in the law. The formation of the cabinet is one of the powers held by the President in a presidential system of government. The research method uses normative legal research with a conceptual approach, a comparative approach, and a statutory approach. The results of the study indicate that the changes in the norms in the Ministry Law are in accordance with the presidential system of government. However, the president's discretion in forming a cabinet must take into account the professionalism, integrity, and track record of ministerial candidates so as not to merely accommodate short-term political interests. Penelitian ini bertujuan untuk membahas tentang kekuasaan presiden dalam pembentukan kabinet. sehubungan dengan adanya perubahan Undang-Undang No. 39 Tahun 2008 tentang Kementerian Negara (UU Kementerian). Salah satu pokok perubahan pada undang-undang tersebut yaitu Pasal 15 terkait jumlah keseluruhan kementerian, yang semula dibatasi paling banyak 34 kementerian berubah menjadi sesuai kebutuhan penyelenggaraan pemerintahan oleh Presiden. Dalam norma tersebut tidak diatur secara eksplisit  mengenai jumlah keseluruhan kementerian. Hal itu memang kompatibel atau sejalan dengan sistem pemerintahan presidensial yang dianut secara tegas oleh Indonesia pasca amandemen konstitusi tahun 2002. Permasalahan yang timbul dari perubahan norma tersebut terkait implikasi pada penambahan jumlah kementerian yang mana berhubungan dengan tata kelola pemerintahan. Perubahan pasal ini mengacu pada legalistik bukan prerogatif sebab jika prerogatif jumlah kementerian tidak perlu diatur dalam UU. Pembentukan kabinet tersebut merupakan salah satu kekuasaan yang dimiliki oleh Presiden dalam sistem pemerintahan presidensial. Metode penelitian menggunakan penelitian hukum normatif dengan pendekatan konseptual, pendekatan perbandingan dan pendekatan undang-undang. Hasil penelitian menunjukkan bahwa perubahan norma pada UU Kementerian sudah sesuai dengan sistem pemerintahan presidensial. Namun, keleluasaan presiden dalam pembentukan kabinet harus mempertimbangkan profesionalisme, integritas dan track record  calon menteri sehingga tidak sekedar mengakomodasi kepentingan politik jangka pendek.